Departmental Institutions and Decentralised Cooperation in Boyacá - Niño Amezquita, José L. (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The Colombian reality shows how subnational entities have been affected by a process of recentralisation since the beginning of the XXI century, and the weakening of intermediate entities in the decentralisation of the last century. However, these entities are seen as the linkage for territorial internationalization, an empty space that few municipalities have adopted and within which departments have hardly acted. Boyacá, a territory in the middle of the Andes, faces challenges that, until now, it has been unable to answer in the right way. The current document is based on primary data which analyses the cooperation from the department as well as the municipalities. Therefore, the internal dynamics and realities suggest that the solution may lie on the integration that Boyacá and its municipalities might have with inter-subnational peers. However, this is still a long path to walk for the Colombian territorial entities, especially in the Department of Boyacá.